Pengaruh Komitmen, Kompetensi dan Good Corporate Governance pada Kinerja Keuangan - Purnama Dewi, Putu Cintya; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 25 No 2 (2018)DO - 10.24843/EJA.2018.v25.i02.p11, 2018)
This research was conducted at Lembaga Perkreditan Desa (LPD) of Abiansemal Sub-district of Badung Regency. The number of samples taken as many as 34 LPD with each chairman of LPD as respondent research. Data analysis technique used in this research is multiple linear regression analysis technique. Based on the results of the analysis found that commitment, competence and good corporate governance significant influence on the financial performance of LPD.Hal indicates that if the commitment and competence of employees the better then the implications on the better the financial performance of LPD.Semakin good corporate governance implementation the better the performance financial LPD. This research also explains that commitment, competence and good corporate governance must be applied to create a solution that will facilitate LPD and other banking companies in improving their performance to improve the welfare of society and related institutions. Kata Kunci: Komitmen, kompetensi, good corporate governance, financial performance